THERAPEUTIC EFFECTIVENESS OF A SIDDHA FORMULATION NILAVAAGAI CHOORANAM: A REVIEW - Jeba Keerthana, *V.Asha; D, Periyasami; Muthukumar, N.J. (International Journal of Ayurveda and Pharma Research, 2018)
Siddha system of medicine is one of the ancient systems of medicine practiced among Tamil speaking community particularly in southern parts of India. The medicine in this system prepared from raw drugs which is obtained from herbals, mineral, metals and animal products. “Nilavaagaichooranam” is one of the Sastric Siddha herbo-mineral preparation with ingredients of 18 herbal and one mineral ingredient. It is used to treat the skin disorders particularly for “Karappan (Eczema)”. This review is aimed to bring out scientific evidence for the therapeutic usuage of “Nilavaagaichooranam” in skin disorders particularly in Karappan (Eczema) and focused on the pharmacological activity responsible for the curative nature of the drug in Karappan (Eczema). Most of the raw drugs used for the preparation of Nilavaagai chooranam have antihistamine activity, anti-inflammatory activity, immunomodulatory activity hence justifying its usage in Karappan (Eczema).